Review paperAllergic diseases – current state of knowledge - Żukiewicz-Sobczak, Wioletta; Krasowska, Ewelina; Zwoliński, Jacek; Sobczak, Paweł; Chmielewska-Badora, Jolanta; Wróblewska, Paula; Piątek, Jacek; Wojtyła, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Allergic diseases are very common in developed countries, particularly among children, adolescents and young adults. Currently, allergies are being considered as an epidemic of the 21st century. According to the Polish Society of Allergology, the percentage of adults suffering from asthma in our country is 5.4%, and in children 10%. The authors describe current knowledge regarding the pathomechanism, incidence, epidemiology and diagnostics of the most common significant allergic diseases, including allergic rhinitis, asthma, allergic conjunctivitis, atopic dermatitis and urticaria. One of the most common allergic diseases is allergic rhinitis, which is the result of an allergic inflammation of the nasal mucosa mediated by immunoglobulin E. Asthma is a lifelong chronic inflammatory disorder of the airways associated with a variety of structural changes occurring in children and adults of all ages. This disease is characterized by bronchial hyperreactivity and obstruction which often disappear either spontaneously or with treatment. Atopic dermatitis is a chronic and relapsing inflammatory skin disease with a varying clinical spectrum, and may often play the role of the first stage of the atopic march. Urticaria is a heterogeneous group of diseases, characterized by the presence of wheals and/or angioedema. The mainstay of allergy diagnosis is in vivo and in vitro testing. In vivo testing includes skin prick tests, prick-by-prick tests, atopy patch tests and also skin application skin test. In vitro testing includes measurement of serum total and antigen-specific IgE using various methods. During the last years, also component-resolved diagnostics have gained growing importance as a useful tool in clinical investigation of IgE-mediated allergies.